Policy Strategies for Spatial Planning in Regional Development of Kisaran City, Asahan Regency, Indonesia: English - Samosir, Abdul Hamid Akhyar; Lubis, Satia Negara; Lubis, Arga Abdi Rafiud Darajat (Asian Multidisciplinary Research Journal of Economy and Learning, 2024)
This study explores the existing conditions and development potential of Kisaran City, Asahan Regency. The analysis includes land use patterns, conformity evaluation with the Regional Spatial Plan (RTRW), and the impact of natural disasters. SWOT analysis and the Analytical Hierarchy Process (AHP) were used to identify the priority of spatial planning concepts in regional development. The results indicate that Kisaran City is still dominated by plantation land with potential risks of fire and flooding. There are discrepancies with the RTRW regarding development that does not align with government predictions. AHP results show the highest priority on decentralization concepts followed by functional integration and growth centers. Recommendations include revisiting the RTRW, strengthening community roles in supporting the economy and tourism, enhancing infrastructure in densely populated areas, and developing growth centers in residential areas with space for new infrastructure. This study provides a comprehensive overview to support structured and sustainable regional development planning for Kisaran City.